Multivariate Analysis of Meristic Characters of Capelin ( Mallotus villosus ) in the Northwest Atlantic - Carscadden, J. E.; Misra, R. K. (Canadian Journal of Fisheries and Aquatic Sciences, 1980)
Counts were made on 11 meristic characters of mature male capelin. The Bonferroni method identified three characters that exhibited significant annual differences. Interpopulation differences were compared using the remaining eight characters, and three capelin stocks were identified. Other studies have tentatively identified at least four stocks, and based on this analysis, meristic characters show only limited promise in separating capelin stocks in the Northwest Atlantic. However, the sequence of statistical procedures used in this study offers potential in other stock discrimination studies.Key words: capelin, Mallotus villosus; meristics, multivariate analyses, Bonferroni method, discriminant function